Implementation of Maintaining Mobility to Reduce the Risk Falls in Elderly - Dian Ratna Elmaghfuroh; Dwi Yunita Haryanti; Roza Rizka Romadhoni (PROFESSIONAL HEALTH JOURNAL, 2024)
Aging is associated with a decline in the physical and cognitive functions of the human body, which also involves the possibility of age-related diseases. Reduced muscle strength and coordination of the lower extremities, accompanied by decreased gait assurance and balance control, are the results of physical deterioration in the aging body. In decreased physiological function, these disorders lead to a higher risk of falls in the elderly. Maintaining mobility is an effort that can be a preventive measure for falls through physical exercise, meeting nutritional needs, and regular health checks. This study aims to determine the effect of palliative care using a maintaining mobility approach to prevent the risk of falls in the elderly at PSTW Jember. This research design is a pre-experimental quantitative research design with a pretest-posttest group design approach with a total sample of 30 elderly people. This research uses analysis of the Wilcoxon statistical test. The research results showed that elderly people who were at risk of falling had a history of musculoskeletal disease of 33.3%, with a p-value of 0.0001. The implementation of maintaining mobility for the elderly can affect the Morse Fall Scale score. In conclusion, there is an effect of maintaining mobility interventions to reduce the risk of falls in the elderly at PSTW Jember.